2015
DOI: 10.1007/s00394-015-1014-y
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre pilot study of iodine status in UK schoolchildren, aged 8–10 years

Abstract: PurposeIodine, as an essential constituent of thyroid hormones, is required for brain development. Iodine status is low in some UK population groups, notably in teenage girls, women of childbearing age and pregnant women. We aimed to assess iodine status of UK schoolchildren as there are no data on children below 14 years of age.MethodsChildren (boys and girls) aged 8–10 years were recruited to a cross-sectional study from schools in three areas of the UK (Omagh, Northern Ireland; Glasgow, Scotland, and Guildf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
(69 reference statements)
3
25
1
Order By: Relevance
“…Correspondingly, a recent study of children of the same age in three UK centres found a UIC of 161 µg/ l in winter (n 134) and 127 µg/l in summer (n 31) (19) , classifying these children as I sufficient with a higher median UIC than that seen in the New Zealand study.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Correspondingly, a recent study of children of the same age in three UK centres found a UIC of 161 µg/ l in winter (n 134) and 127 µg/l in summer (n 31) (19) , classifying these children as I sufficient with a higher median UIC than that seen in the New Zealand study.…”
mentioning
confidence: 74%
“…We suggest that, for consistency, the IGN should define I status using children of the same age groups across countries, and that the 2016 IGN scorecard should define the UK as having sufficient I status among children based on the UIC of 161 µg/l found in 8-10-year-old children (19) . However, adequate status among children does not mean that the whole population has a sufficient intake, as seen in both the UK and New Zealand, where intakes for adults and children are adequate but pregnant and lactating women have insufficient intakes.…”
mentioning
confidence: 99%
“…The data demonstrate that the food group 'milk and milk products' is the principal source of iodine in the UK diet and that milk is the individual product contributing most to the population's intake. Positive associations between milk intake and the iodine status of children (Bath et al 2016), adolescents (Vanderpump et al 2011), pregnant women (Bath et al 2014a) and women of childbearing age (Bath et al 2014b) provide further evidence for the important contribution of milk to iodine intake in the UK. The average iodine content of conventional UK cows' milk is 44 lg/100 g (SACN 2014), and this means that just over 300 ml of milk would be enough to meet the UK recommendation of 140 lg of iodine per day for an adult.…”
Section: Dietary Sources Of Iodine Including Milkmentioning
confidence: 89%
“…Positive associations between milk intake and the iodine status of children (Bath et al . ), adolescents (Vanderpump et al . ), pregnant women (Bath et al .…”
Section: Dietary Sources Of Iodine Including Milkmentioning
confidence: 99%
“…Some complications of iodine deficiency include goitre, lack of physical and mental development, and poor learning ability in children (9)(10)(11) . Iodine deficiency also leads to abortion, stillbirth and congenital anomalies, and increases prenatal death and infant mortality (1,(12)(13)(14) . IDD are preventable using methods such as iodized salt (15,16) .…”
mentioning
confidence: 99%